QTc Interval Prolongation and Life-Threatening Arrhythmias During Hospitalization in Patients With Coronavirus Disease 2019 (COVID-19): Results From a Multicenter Prospective Registry. (24th October 2020) - Santoro, Francesco; Monitillo, Francesco; Raimondo, Pasquale; Lopizzo, Agostino; Brindicci, Gaetano; Gilio, Michele; Musaico, Francesco; Mazzola, Michele; Vestito, Domenico; Benedetto, Rossella Di; Abumayyaleh, Mohammad; El-Battrawy, Ibrahim; et al.
Abstract: Background: Prolonged QTc intervals and life-threatening arrhythmias (LTA) are potential drug-induced complications previously reported with antimalarials, antivirals, and antibiotics. Our objective was to evaluate the prevalence and predictors of QTc interval prolongation and incidences of LTA during hospitalization for coronavirus disease 2019 (COVID-19) among patients with normal admission QTc. Methods: We enrolled 110 consecutive patients in a multicenter international registry. A 12-lead electrocardiograph was performed at admission, after 7, and at 14 days; QTc values were analyzed. Results: After 7 days, 15 (14%) patients developed a prolonged QTc (pQTc; mean QTc increase 66 ± 20 msec; +16%; P < .001); these patients were older and had higher basal heart rates, higher rates of paroxysmal atrial fibrillation, and lower platelet counts. The QTc increase was inversely proportional to the baseline QTc level and leukocyte count and directly proportional to the basal heart rate ( P < .01). We conducted a multivariate stepwise analysis including age, male gender, paroxysmal atrial fibrillation, basal QTc values, basal heart rate, and dual antiviral therapy; age (odds ratio [OR], 1.06; 95% confidence interval [CI], 1.00–1.13; P < .05), basal heart rate (OR, 1.07; 95% CI, 1.02–1.13; P < .01), and dual antiviral therapy (OR, 12.46; 95% CI, 2.09–74.20; P < .1) were independent predictors of QT prolongation. The incidence rate of LTA during hospitalization was 3.6%. There was 1 patient who experienced cardiac arrest and 3 with nonsustained ventricular tachycardia. LTAs were recorded after a median of 9 days from hospitalization and were associated with 50% of the mortality rate. Conclusions: After 7 days of hospitalization, 14% of patients with COVID-19 developed pQTc; age, basal heart rate, and dual antiviral therapy were found to be independent predictors of pQTc. Life-threatening arrhythmias have an incidence rate of 3.6%, and were associated with a poor outcome. Abstract : After 7 hospitalized days, 14% of coronavirus disease 2019 patients developed prolonged QTc, for which age, basal heart rate, and dual antiviral therapy were independent predictors. Life-threatening arrhythmias have a 3.6% incidence rate, and were associated with a poor outcome.